DEVELOPMENT OF IMMERSIVE ENVIRONMENT WITH CONTROLLED DEPTH PERCEPTION IN AUGMENTED REALITY APPLICATIONS - A.V. Ivaschenko; M.V. Aleksandrova (Модели, системы, сети в экономике, технике, природе и обществе, 2023)
Background. The paper discusses an actual problem of ensuring the immersiveness of human-computer interaction in the Augmented Reality environment by controlling the depth of immersion. Materials and methods. The article proposes a model of an immersive environment, which, unlike analogues, allows controlling and managing the depth of user immersion, taking into account his individual characteristics of Augmented Reality perception. The user's reaction is tracked using the oculography (eye-tracking) system or by intelligent recognition of emotions based on the results of image recognition of facial expressions. The model is based on the implementation of the accented visualization method and expands the possibilities of its practical application in the tasks of improving the convenience of virtual and augmented reality interfaces, medical rehabilitation and control of manual operations in production, maintenance and repair. Results. An immersive environment model with a controlled depth of immersion processes the event chains of user attention fixation and changing the state of virtual and real objects in space and time, which makes it possible to monitor the basic parameters that characterize user perception: focus, relevance, and instability. On the basis of the proposed model, a control system was implemented that ensures the achievement of a statistical correspondence between the tempo-rhythms of the processes of recognition, classification and adequate action in relation to real and virtual objects. Conclusions. The main challenges of losing the depth of user immersion in the immersive reality environment include the discrepancy between the contexts of virtual and real elements and the user experience, the difference between the pace of events taking place in virtual reality and the pace of real events or the user's readiness, and the presence of distractions that affect the loss of involvement and decrease in perception. The choice of the solution depends on the dynamics of changes in parameters.